Financial analysis of performance of agribusiness firms listed on the KLSE - Ilmas Abdurofi, . (2014)
Agriculture in Malaysia is one of the potential sectors that contribute to the country’s Gross Domestic Product (GDP). Since the declining trend of agriculture sector, Malaysian Government plan (2012) focuses on developing the country’s agricultural sector by providing various forms of support and schemes in encouraging investments. Many agribusiness firms that are registered in the Malaysian capital market are hoping to achieve good results by acquiring tremendous capitals since an improved company performances relate positively to stock returns. There are numbers of variables that contribute to the effect of the stock returns between using technical and fundamental analysis. Financial ratio variables, as one of fundamental analysis, involves the construction of the ratios using specific element from financial statements in ways that help identify the strengths and weakness of the firm and also may predict the stock return. Many researchers investigated the relationship between financial ratios and stock return that indicate the connection between financial ratios and stock return is normally related. Nevertheless, some of the researchers found that the connection sometimes is not existed. The objectives of this study is to analyze the effect of financial ratios on the return of agribusiness stocks, investigate the performance of Malaysian agibusiness sectors, determine the industry ratios of agribusiness firms and compare the effect of financial ratios between the total stock return and capital gain. The financial ratios on this study consist of Dividend Yield (DY), Earning Yield (EY), Book-to Market (BM), Debt-to Equity Ratio (DER) and Return on Asset (ROA). The research focused on agribusiness firms in Bursa Malaysia or Kuala Lumpur Stock Exchange (KLSE). The data used quantitative data, that is, secondary data on financial statements and stock price from agribusiness firms in the Malaysian Stock Exchange Statistics from 2006 to 2012. The process of collecting data was filtered by using six criterias that employed 40 agribusiness firms. Panel data regression techniques was conducted to estimate the relationship between the independent and dependent variables using data analysis and statistical software. The study also applied generalized least squares (GLS) and ordinary least square (OLS) method to correct set of covariance t-statistic and tackle the heteroskedasticity and nonnormality distributed residuals. The findings showed that, the overall agribusiness performance in terms of profitability, leverage and market ratios was fluctuated from 2006 to 2012, where there are significant difference performance between the period 2006-2008 and the period 2009-2012. Next, the value of agribusiness industry ratio from variable DY, EY, BM, DER, and ROA are 3.98%, 9.36%, 1.3, 0.7, and 8.95% respectively. Furthemore, the study found the evidance that the individual financial ratios as DY, EY, BM and ROA are able to predict future total stock return and capital gain, where the result has the similar findings from the previous researchers that the BM variable contributed as the highest predictive power and the combination of the financial ratios had significant predictability to forecast future total stock return and capital gain, also enchanced the predictive power to explained those dependent variables. Eventually, the total stock return and capital gain had a similarity to be predicted by financial ratios, where the slight differences solely emerged through both of the slope coefficient and adjusted R2. Since the differences was not outlying and imperative contribution was identical, both of the total stock return and capital gain are the proper parts of stock return theory that may accurately be predicted. In addition, as a suggestion to future investors, before investing the money, investor needs to investigate any output of company’s financial ratios as a fundamental background to appraise future stock investment, since the relationship between financial ratios and stock return are correlated. Furthermore, the relation of dividend yield to stock return was negative, denoting that the firms focused solely to the long term profit by holding the firm’s capitals. Hence, the study recommended that the agribusiness firms should also considered sharing tremendous dividends in the short term to attract more potential investors. Finally, the outcomes were elaborated that the capital expenditure of agribusiness firms are quitely excessive and urge the company to lend huge capital from outsider, the study also suggested the Government to create some of the agricultural policies to provide several incentives in terms of production cost or intial cost in order to reduce the company’s debt.